SOME ASPECTS OF DEVELOPMENT OF HOSPITAL PHARMACY ABROAD - Y. V. Miroshnichenko; S. Z. Umarov (Исследования и практика в медицине)
We considered a number of aspects of the development of hospital pharmacy abroad. It is revealed that the focus of professional pharmaceutical associations in the information and educational fields creates the basis for creation of strategy of development of hospital pharmacy. The analysis of population dynamics of pharmaceutical staff in hospital pharmaciesis held, and the detailed characteristics of activities of certain categories of specialists of hospital pharmacies is presented.